2014
DOI: 10.1016/j.virol.2014.03.010
|View full text |Cite
|
Sign up to set email alerts
|

E1B and E4 oncoproteins of adenovirus antagonize the effect of apoptosis inducing factor

Abstract: Adenovirus inundates the productively infected cell with linear, double-stranded DNA and an abundance of single-stranded DNA. The cellular response to this stimulus is antagonized by the adenoviral E1B and E4 early genes. A mutant group C adenovirus that fails to express the E1B-55K and E4orf3 genes is unable to suppress the DNA-damage response. Cells infected with this double-mutant virus display significant morphological heterogeneity at late times of infection and frequently contain fragmented nuclei. Nucle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 112 publications
(148 reference statements)
1
8
0
Order By: Relevance
“…The Ad E1B-55K and E4orf6 proteins cause degradation of various DDR proteins and E4orf3 expression leads to removal of the MRN DNA damage sensor complex from viral replication centers [ 33 , 38 , 39 ]. Moreover, while Ad was shown to induce parylation, the intracellular distribution of PAR-modified proteins was altered by the E1B-55K and E4orf3 proteins, possibly resulting in further modulation of the DDR [ 73 ]. The virus also utilizes its core protein VII to protect the incoming genome from the DDR [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…The Ad E1B-55K and E4orf6 proteins cause degradation of various DDR proteins and E4orf3 expression leads to removal of the MRN DNA damage sensor complex from viral replication centers [ 33 , 38 , 39 ]. Moreover, while Ad was shown to induce parylation, the intracellular distribution of PAR-modified proteins was altered by the E1B-55K and E4orf3 proteins, possibly resulting in further modulation of the DDR [ 73 ]. The virus also utilizes its core protein VII to protect the incoming genome from the DDR [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…As a consequence it has been used to facilitate the display proteins on the surface of the viron (Meulenbroek et al, 2004). In contrast it has recently been demonstrated that pE1b_55K is involved in the inhibition of apoptosis inducing factor to prolong the life of infected cells (Turner et al, 2014). Given these somewhat disparate roles in AdV infection it would seem unlikely the pIX_E1b_55K fusion acts as a multiple function protein.…”
Section: Discussionmentioning
confidence: 99%
“…FG12-derived plasmids for targeting of AIF and LacZ by RNA interference (RNAi) have been rigorously assessed and used as described [ 28 , 48 , 49 ]. Lentiviral packaging plasmids pRRE, pRSV-rev, and pHCMV-G are as described [ 50 ].…”
Section: Methodsmentioning
confidence: 99%